TNFRSF13B VARIANTS ACT AS MODIFIERS TO CLINICAL PHENOTYPES IN COMMON VARIABLE IMMUNE DEFICIENCY DISORDERS - Sinem Fırtına; Aslı Kutlu; Begüm Işıkgil; Medinenur Yozlu; Beyza Nur Cepeci; Hülya Yılmaz; Yuk Yin Ng; Özden Hatırnaz Ng; Ayça Kıykım; Esra Özek Yücel; Elif Karakoç Aydıner; Safa Barış; et al. (Sabiad)
Objective: The TNF receptor gene 13B (TNFSRF13B) is a member of the TNF superfamily which is crucial for B cell maturation, plasma cell differentiation, and antibody response. Impaired expression of the TNFRSF13B gene is associated with common variable immune deficiency (CVID), autoimmunity, and lymphoproliferation disorders. Besides the disease-causing variants of this gene, its different isoforms are associated with strong and weak TNFRSF13B expression that leads to an unbalanced B cell response.Materials and Methods: The study detected 26 variants (three synonymous, five missenses, eleven UTR, and seven intronic variants) in the TNFRSF13B gene by screening 68 CVID patients with targeted next generation sequencing. An integrative bioinformatics approach was utilized to provide a plausible explanation for CVID associations from different perspectives and to investigate the associations from the clinical findings.Results: Fifty-eight percent (15/26) of the detected variants were altered regulatory elements, such as transcription factor binding, miRNA binding sites, splice site regions or the thermodynamic impact on protein. We observed that patients who suffered from the potential splicing variants had significantly low IgA levels (p=0.009), autoimmunity (p=0.02) and gastrointestinal findings (p=0.05). In addition, the c.*79A>G 3-UTR variant was found with the low IgA and IgE levels. Thirteen variants found to have at least tenfold increased allele frequencies as compared to global databases indicating that the TNFRSF13B variants, which have a potential regulatory effect, are more common in CVID patients.Conclusions: All findings suggested that these variants may not be the causative variant for the CVID phenotype but the unbalanced TNFRSF13B alternative splices could contribute to the pathogenesis of patients independent from the underlying genetic background of CVID.